ALA-PDT combined with 2940 nm ablative fractional Er:YAG laser for Darier's disease - Tingting Gao; Junyan Xiao; Na Pan; Fan Xia; Xianyu Zeng; Li Qin (Photodiagnosis and Photodynamic Therapy)
Darier's disease is a rare, genetically determined dyskeratotic skin disorder. Although many conventional treatments have been reported, management of Darier's disease remains challenging. Most patients are at high risk of recurrence during long-term follow-up. Here, we present two patients who were successfully treated with ALA photodynamic therapy (PDT) and ablative 2940 nm Er:YAG fractional laser. Both patients exhibited significant improvements in the affected areas with moderate pain, transient erythema and edema. Remission durations of up to 2 years were observed in both patients after combination treatment. Our findings suggest that the combination of ALA-PDT and 2940 nm fractional Er:YAG laser may be an effective, safe and well-tolerated treatment option for Darier's disease.